2014
DOI: 10.1093/jjco/hyu088
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Superior Gingivobuccal Sulcus: An 11-Year Institutional Experience of 203 Cases

Abstract: Patients with higher stage tumours who underwent infratemporal fossa clearance showed better overall and disease-free survival than those who did not undergo infratemporal fossa clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
4
0
2
Order By: Relevance
“…Study is comparable with study of Nayak et al [14] and Lekawale et al [15] From these studies, it is found that most of the SCCs of oral cancer patients present at fifth decade of age. In this study male-to-female ratio was 5:1, which is comparable with that in studies conducted by Iype et al [6] and Dewan et al [16] In this study, the incidence of SCC of the gingivobuccal complex was recorded to be maximum in businessmen (23.33%) followed by housewives and labourers (13.33% each). The is compared with other similar studies.…”
Section: Discussionsupporting
confidence: 90%
“…Study is comparable with study of Nayak et al [14] and Lekawale et al [15] From these studies, it is found that most of the SCCs of oral cancer patients present at fifth decade of age. In this study male-to-female ratio was 5:1, which is comparable with that in studies conducted by Iype et al [6] and Dewan et al [16] In this study, the incidence of SCC of the gingivobuccal complex was recorded to be maximum in businessmen (23.33%) followed by housewives and labourers (13.33% each). The is compared with other similar studies.…”
Section: Discussionsupporting
confidence: 90%
“…Os tumores em região oral e de orofaringe estão entre os mais frequentes 11 , sendo responsáveis por mais de 219 mil mortes em todo o mundo, anualmente 12 . Aproximadamente 90% dessas malignidades correspondem ao CCE 13 , onde a língua é acometida em 44% dos casos 14 . No presente caso, a lesão encontrava-se na borda lateral da língua.…”
Section: Discussionunclassified
“…This was comparable with a study by Iype et al reporting ratio of 6.7:1 and a study by Dewan et al reporting ratio of 5.77:1. 12,13 Higher proportions of drinkers and/or smokers amongst males than females explains the male preponderance in oral premalignant lesions and oral malignant lesions. Oral premalignant lesions and oral malignant lesions were highly prevalent in cases of labourers and unemployed.…”
Section: Discussionmentioning
confidence: 99%